An, Analysis BAHASA ARAB SEBAGAI PENJAGA TRADISI DAN MEDIUM BUDAYA ISLAM: TINJAUAN TEORETIS DAN HISTORIS DI INDONESIA - Hayatun Nissa; Dewy Sartika; Erlina; Zainal Rafli; Rahmad Khusen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article analyzes the role of the Arabic language as a guardian of tradition and a cultural medium of Islam in Indonesia through a synthesis of historical and theoretical perspectives. Arabic has served as an essential foundation of Islamic civilization, spreading to the Nusantara through trade routes as early as the 9th century and undergoing acculturation with local cultures. Its development occurred gradually, beginning with its liturgical function among early Muslim communities, followed by administrative and scholarly uses during the era of Islamic kingdoms, and later its institutionalization through pesantren and modern educational institutions. This study employs a descriptive qualitative approach based on a literature review to interpret historical texts, religious sources, and scholarly works related to the development of Arabic. The analysis is carried out using content analysis techniques to identify historical patterns, social functions, and the symbolic meanings of Arabic within Indonesian Muslim society. The findings indicate that Arabic functions not only as a means of communication but also as symbolic capital that shapes collective identity through rituals, arts, vocabulary, and cultural practices. In the era of globalization, Arabic faces challenges due to the dominance of global languages and traditional learning methods, yet it is also experiencing revitalization through digital technologies, social media, and the strengthening of academic and sharia economic fields. The study concludes that Arabic possesses strong resilience and continues to adapt to modern contexts, thus remaining a central medium for preserving tradition, transmitting knowledge, and reinforcing the religious identity of Indonesian Muslim communities.